PENDAMPINGAN PEMBUATAN PROPOSAL PENELITIAN TINDAKAN KELAS (PTK) PADA GURU DI SMA SRIJAYA NEGARA PALEMBANG - Dewi Pratita; Dewi Koryati; Ikbal Barlian; Deskoni Deskoni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2019)
The teaching profession is a complex and challenging profession. In addition it must be competent and mastered the science that was involved, teachers also charged must be capable of creative, innovative, and inspiring when teaching in the classroom. It is not easy to become a professional. As a professional teacher who dedicated himself to education, teachers must be routinely adding their knowledge by reading and writing. Thereby you can summarize the valuable experience for the important things like understanding the instructional design, understanding learning styles of students, as well as the utilization of the internet in learning.Activities conducted by teachers such as these can be poured in a classroom research conducted by teachers through Classroom Action Research activities or better known as PTK. The purpose of the the activities of this devotion is producing material on how that can be done by teachers in improving the professionalism of teachers in the High School State Srijaya Palembang through Class Action Research Activities (PTK). This devotion activities carried out in the High School State Srijaya Palembang and followed by 20 teachers from a variety of different fields of study. A model of devotion used was mentorship with methods of delivery of material concerningthe Class Action Research (PTK). Evaluation test of understanding PTK with an average of 50 increased to 58.5 in the final test. The increase in accompanied by a very strong interest of participants to be able to make and carry out research activities actions class amounted to 87%. The conslusion of this activity the participants enthusiastically follow the activities of mentoring to improve the ability of professional teachers.